Key concepts in ethnography - O'Reilly, Karen (Los Angeles SAGE, 2009)
This title addresses and summarizes the basic and related issues in ethnography, examines topics like 'sampling' and 'generalizing' as well as embracing new fields such as virtual, visual and multi-sighted ethnography, and discusses time-honoured themes such as key informants, access, participant observation and rapport as well as key contemporary issues such as reflexivity, writing, and ethics.
Keywords: Ethnology; Ethnology -- Philosophy